PERMAINAN PAPAN FLANNEL TERHADAP KEMAMPUAN MENCOCOKAN ANGKA, WARNA, DAN GAMBAR DAN MELATIH MOTORIK HALUS PADA SISWA PAUD - Dzulkifli Dzulkifli; andini dwi arumsari (MOTORIC, 2022)
FLANNEL BOARD is a learning media in the form of an educational game tool (APE) which aims to help early childhood in learning to recognize numbers, objects and know colors. This game is also designed to train fine motor skills in PAUD students. This research uses the type of experimental research. The data collection technique used in this research is observation with descriptive method. This research was conducted at PAUD Tunas Mulia which is located on Jl. Rangkah Buntu I No. 1, district. Tambaksari, Surabaya. The subjects in this study were 10 PAUD Tunas Mulia students aged 4 years. The results of the study are that after the researchers carried out treatment for 5 times in a row for 3 days in the morning at the same time on the first day to the third day using the Flannel Board that the researchers made and the results of observations showed that the subjects experienced an increase in basic recognition skills. numbers, objects and knowing colors – as well as improving the subject's fine motor skills. Keywords: Educational game tools, number recognition ability, ability to distinguish colors, fine motor skills.